О производной ряда Дирихле - Šeremeta, M. N.; Fedyniak, S. I. (Mathematical Modelling and Analysis, 1996)
“О производной ряда Дирихле” Mathematical Modelling Analysis, 1(1), p. 76-78. Article in Russian. First Published Online: 14 Oct 2010